Islam dan Budaya Banten - Irfani, Fahmi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
Banten is one of the oldest centers of Islamic culture in Indonesia. Acculturation, assimilation, and dijjuslon represent something that is inevitable between Islam and local culture, thus showing a typical culture. This area is also known for its magical atmosphere of the place in search of knowledge lc:anuragan, supernatural power, as a form of debus culture reflection. Clerics, warlords kiyai, and jawara, are symbols of this region, and they occupy the position of the central figures in the social stratification of local communities. Kiyai and the Jawara of an honorary degree from the traditionalist Islamic groups are not only seen as religious figures, but also as charismatic community leaders. Their authority often exceed the power of the formal leader of an elite government. These exponents that characterize public offerings and bring to as different regions in the archipelago, mainly due to the unique culture, local tradition that integrate culture with Islam.